Association between Maternal-Neonatal Separation Stress and the Development of Algias in Preclinical Trials: An Integrative Literature Review - Pedro Isac Fontenele Saldanha; Felipe Dantas Silveira; Paula Goes; Mirna Marques Bezerra; Hellíada Vasconcelos Chaves (Archives of Current Research International, 2024)
Introduction: Maternal separation (MS) is a frequent neonatal stress experience, given the diverse social inequalities and needs in modern society. It is known that social losses or separations are experiences that considerably affect people’s psychological patterns, but there is still no review of the associations between the stress caused by the separation of mothers from their children and its impact on the onset or increase in pain. From this perspective, the study in question aimed to review the literature in an integrative manner to seek to elucidate the association between neonatal MS and the onset or increase in pain in later stages of life, in animal models. Methodology: For this purpose, the PubMed, Web of Science, Embase, Scopus, Lilacs and Google Scholar databases were used, without date or language restrictions, to search for related literature, using the “PICO” strategy. Results: A total of 843 articles were found and, after applying inclusion and exclusion criteria, a total of 35 articles were selected for this review, all of which were in animal models. Evidence indicates that the experience of neonatal MS is associated with the development of not only psychological but also neurophysiological disorders, which tend to reduce the threshold of sensitization of nociceptors, amplifying their receptivity to stimuli, generating painful sensations of varied natures and through different mechanisms, inherent to each type of pain generated. Conclusion: However, despite advances in research, new studies still need to be conducted focused on Orofacial Pain, since there is only one study on this topic.